(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The Stabilization entails any change whichkind of modifies or renders the soil or any other substanceThe purpose of Stabilizing soil is to increase the strength ofsoil and also as improve resistance for softening throughwater bond and these soil particles systematized, also waterproofing the particles or both combined together. The use ofcement and lime was used for very long time in previoustimes and it was working well and had enormousadvantages but now the use of cement is used less becauseof the cost of cement and contrary effects on theenvironment from its manufacture. Stabilizing is quitedifferent from modification which implies only a minorchange in properties of soil or rock The increasing harm ofemitting of co2 through cement manufacturing also thegrowing cost of additives has lead to the rise of growth ofother stabilization such as plastic materials, ash of wood orrice cover, glass fiber, etc.